2016
DOI: 10.1007/s00421-016-3439-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of repetition mechanics on the adaptations resulting from strength-, hypertrophy- and cluster-type resistance training

Abstract: PurposeThe purpose of this study was to examine the acute and chronic training responses to strength-, hypertrophy- and cluster-type resistance training.MethodsThirty-four trained males were assigned to a strength [STR: 4 × 6 repetitions, 85 % of one repetition maximum, (1RM), 900 s total rest], hypertrophy (HYP: 5 × 10 repetitions, 70 % 1RM, 360 s total rest), cluster 1 (CL-1: 4 × 6/1 repetitions, 85 % 1RM, 1400 s total rest), and cluster 2 (CL-2: 4 × 6/1 repetitions, 90 % 1RM, 1400 s total rest) regimens whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 38 publications
(60 reference statements)
2
27
0
4
Order By: Relevance
“…Our results are in line with those of previous studies that have shown lower velocity loss and lactate concentrations after four different resistance exercise protocols (varying volume and relative load) using 10 and 20 s IRR compared to traditional training sets of full squats performed in a smith machine [13], and greater ability of the subjects to maintain mean velocity and peak power when performing cluster sets of 30 s compared to traditional sets in the free-weight back squat exercise [12]. In addition, lower velocity loss and lactate concentrations were also found when comparing two strength-and hypertrophy-oriented TSC protocols against two different strength-oriented CSC protocols with different relative loads and 25 s IRR for the back squat exercise [17]. Similar to the above findings, CSC protocols analyzed in upper-body movements have also found lower drops in velocity and lactate concentrations for the bench press exercise when performing four sets of five repetitions with 30 s IRR compared to four sets of five repetitions using a TSC without IRR [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in line with those of previous studies that have shown lower velocity loss and lactate concentrations after four different resistance exercise protocols (varying volume and relative load) using 10 and 20 s IRR compared to traditional training sets of full squats performed in a smith machine [13], and greater ability of the subjects to maintain mean velocity and peak power when performing cluster sets of 30 s compared to traditional sets in the free-weight back squat exercise [12]. In addition, lower velocity loss and lactate concentrations were also found when comparing two strength-and hypertrophy-oriented TSC protocols against two different strength-oriented CSC protocols with different relative loads and 25 s IRR for the back squat exercise [17]. Similar to the above findings, CSC protocols analyzed in upper-body movements have also found lower drops in velocity and lactate concentrations for the bench press exercise when performing four sets of five repetitions with 30 s IRR compared to four sets of five repetitions using a TSC without IRR [18].…”
Section: Discussionmentioning
confidence: 99%
“…The literature analyzing chronic responses to cluster training compared to traditional protocols seems controversial. Some studies show greater improvements in barbell velocity and power output [11,15] and muscular strength [15], while others have not found differences in the improvements in strength, jump height, and mechanical variables between protocols [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This type of training has been used over the years occupying high volume load protocols (muscular endurance) 45,46 , high-intensity exercises (maximum strength) 47,48 , or muscular hypertrophy programmes 12,13 . In this sense, it has been reported that high volume muscle endurance training performed at a low-intensity of 1RM increases DOMS levels in healthy sedentary subjects (p < 0.05), regardless of whether it is performed with short intervals (1 minute) or long intervals (3 minutes) of rest between series 36 .…”
Section: Conventional Strength and Muscle Fatigue Trainingmentioning
confidence: 99%
“…In order to achieve optimal development of strength, power and muscular hypertrophy, traditional [7][8][9][10][11][12][13] and non-traditional training methods have been used, including plyometric exercises on land [14][15][16][17][18] , plyometrics in the aquatic environment 19 , occlusion training [20][21][22][23] , training with elastic bands 24 , electrostimulation training 11 , eccentric exercises 25 , and Bodypump® programs 26,27 . These methods have demonstrated, in several cases, increases in sports performance 4,25,27 .…”
Section: Introductionmentioning
confidence: 99%
“…These results were maintained even when the training variables (intensity x volume) did not change. The low RPE scores during cluster-set are associated with the pause between repetitions (Hardee et al, 2013), which results in decreased metabolite concentrations for this type of training (Nicholson, Ispoglou, & Bissas, 2016). This direction may also influence the improvement of pleasure during the proposed activity (Alves et al, 2015) and may be an option that contributes to the maintenance or increase the intensity of training without impair the predetermined repetitions (Tufano et al, 2017).…”
Section: Introdutionmentioning
confidence: 99%